Instructional Strategies for E-Training Module: A Self-Determination Theory Perspective - Rahim R.E.A.; Mokhtar S.; Din N.Md. (Elsevier B.V., 2025)
The use of online training or e-training is becoming popular in higher education institutions, with physical attendance of training being substituted by online mode. While the provisions of e-training are widely available, their completion rates are, however, low. Research evidence suggests that motivation is a contributing factor. The online module of the e-training should be designed in such a way as to promote learners' motivation to engage and complete the course. One way to explore motivation is through the lens of the Self-Determination Theory (SDT). We review previous studies on the application of the SDT in instructional strategies for learners' motivation and engagement. Based on the review, we propose a self-determined instructional strategy of e-training module for higher education. Finally, the implications and future studies are presented. ? 2023 The Authors. Published by Elsevier B.V.